NOMENCLATURE AND TYPIFICATION OF VARIOUS MYRTACEAE OCCURRING IN SOUTHEAST ASIA - Parnell, J.; Soh, W. K. (Edinburgh Journal of Botany, 2018)
The nomenclature of a number of taxa that occur in Southeast Asia in Baeckea, Decaspermum, Leptospermum, Melaleuca, Psidium, Rhodamnia, Rhodomyrtus and Tristaniopsis is discussed: eight lectotypes are designated, six taxa are shown to have been previously lectotypified under Article 9.9 with second-stage lectotypification being deemed unnecessary for two of them, and comments are made on two species that we cannot yet typify.